2014
DOI: 10.1136/heartjnl-2014-306160
|View full text |Cite
|
Sign up to set email alerts
|

The hazard of rounding Cape Horn: is it changing?

Abstract: …he who goes the oftenest round Cape Horn goes the most circumspectly.Herman Melville, "White-Jacket", 1850Notwithstanding the range of strategies to help one cope with the cold weather, most countries experience mortalities in excess of 5-30% in winter, brought on mainly by cerebrovascular events. 1 This variability is mainly attributed to the population being able to keep themselves warm, both indoors and outdoors, necessitated by the mean cold temperature. Policies and measures to increase efficient use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This phenomenon has also been reported from a large study where seasonal changes were more marked in rural areas 6 . Overall, the mean difference between winter and summer was more extreme in the rural than in the urban areas in that study (12 vs. 8 mmHg; p for interaction <0.0001).This may be due to the fact that rural population is worse affected by season change due to lack of adequate housing and central heating 5, 25. Also, More number of people were heavy workers in rural as compared to urban areas (17.7% vs 0.2%, respectively) who work in extreme outside weather conditions.…”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon has also been reported from a large study where seasonal changes were more marked in rural areas 6 . Overall, the mean difference between winter and summer was more extreme in the rural than in the urban areas in that study (12 vs. 8 mmHg; p for interaction <0.0001).This may be due to the fact that rural population is worse affected by season change due to lack of adequate housing and central heating 5, 25. Also, More number of people were heavy workers in rural as compared to urban areas (17.7% vs 0.2%, respectively) who work in extreme outside weather conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies suggest that overall adverse health impacts of winter cold in high-income countries may be decreasing in recent decades due to better housing and improved health care 33 34 . However, our observation of a strong cold effect on hypertension in Ontario showed that adverse effect of cold on cardiovascular conditions remained persistent in current days.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-city study in China showed that the optimum temperature was 17.7 °C in the Northeast, 19.5 °C in the North, 18.2 °C in the Northwest, 23.4 °C in the East, 21.1 °C in the Central part, 26.5 °C in the Southwest and 27.4 °C in South China [ 18 ]. This heterogeneity may be owing to the difference of the latitude of the cities and the lifestyle of residents in the cities [ 47 ]. Furthermore, these differences may influence the physiological adaptation and behavioral adaptation of the population.…”
Section: Discussionmentioning
confidence: 99%